POLA DISTRIBUSI KASUS OSTEOARTRITIS DI RSU DOKTER SOEDARSO PONTIANAK PERIODE 1 JANUARI 2008 - 31 DESEMBER 2009 - ., Maria Isabella Arissa (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2013)
Background: Osteoarthritis is known as a degenerative process that happens in bone joints and can affect one or more joints. Osteoarthritis is caused by several factors, mainly age and gender. A quarter of the whole female population and fifth of the whole male population with age over 60 years can suffer from osteoarthritis. Osteoarthritis can be found in all bone joints, eventhough most are found in joints that receives extra wear.Aim: To know the pattern of distribution of osteoarthritis based on gender, location and age in RSU dr. Soedarso Pontianak.Method: The design used in this is study is a descriptive cross-sectional.Results: Normality test of Skewness and Kurtosis was found to be 0,165 and 0,329. Osteoarthritis is found more commonly in women (68,67%) than men (31,33%). Based on location, osteoarthritis is found mostly in the knee joint (89,91%). Highest prevalence is found in patients ages 55-60 years (28,93%). Conclusion: Osteoarthritis is found more commonly in women than men within range of age 55,73 years. Osteoarthritis is found mostly in the knee joints.Keywords: Pattern of distribution, Osteoarthritis, RSU dr. Soedarso Pontianak, 2008/2009